Efek Pemberian Ekstrak Kulit Kabau (Archidendron jiringoides komariah) Terhadap Konsentrasi Spermatozoa Mencit Jantan yang Diinduksi Timbal (Pb) - Elisa Nurma Riana; Yanti Ariyanti (Universitas Pendidikan Ganesha, 2024)
Infertility is currently an important problem in the world, including in Indonesia. Infertility can occur in men and women. Inmen, factors causing infertility can come from external sources. One environmental factor that can cause infertility is exposureto heavy metals from the environment. One way to prevent and treat infertility includes consuming natural antioxidants derivedfrom plants. One plant that has antioxidant compounds and has antioxidant activity is the kabau plant. This research wasconducted to test the effect of kabau seed pod extract (Archidendron jiringoides Komariah) on male mice exposed to Pb metalto determine its effect on the concentration of spermatozoa in male mice. The methods used in this research include:preparation of test animals, making simplicia and kabau seed pod extract, exposing the extract to test animals, isolatingorgans, and making spermatozoa suspensions. Giving kabau seed pod extract to mice that had previously been exposed tolead (Pb) increased the concentration of mice spermatozoa with the most effective dose of kabau bark extract, namely 190mg/kg BW. However, statistical analysis shows that the increase is not significant.